Coherence in psychotic discourse - Ribeiro, Branca Telles (Oxford studies in sociolinguistics., 1994)
This monograph investigates ways of establishing coherence in the discourse of a thought-disordered patient, by analyzing two interviews - one where the patient is in an acute psychotic state, and the other where the same patient is considered fully recovered.